FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU KEBIASAAN JAJAN ANAK SEKOLAH DASAR NEGERI DI KECAMATAN WONOSARI KABUPATEN BOALEMO - Daniel Robert; Ni Wayan Sudarti (Jurnal GIZIDO, 2014)
Human behavior is derived from the impulse in man, was a boost is an attempt to meet theneeds that exist in human beings. Eating behavior is often the problem is the habit of eating inthe cafeteria or stalls around the school and the habit of eating fast food. The role of street foodin contributing to energy or energy substances and proteins are highly significant, given thatschool children are generally less food protein circumstances and the children often snack, itshould hawker food sold dikantin school is a food that contains a lot of protein.Types of non-experimental research with survey approach and observational with crosssectional sample of 88 students. The data collected is the behavior of eating habits, nutritionalknowledge, the habit of breakfast in the morning, the frequency of breakfast habits, habits takestock, pocket money, and the type of food, obtained through a questionnaire. Data analysisusing Chi Square test.Results there is a relationship between knowledge and habit of eating snacks children, there isa relationship between habitual breakfast with the habit of eating snacks, there is a relationshipbetween habitual bring food to the habit of eating snacks, there is a relationship between alarge allowance with habit of eating snacks children, there is a relationship between a largeallowance to customs snacks, and no association with the type of street food snack habits ofprimary school children in the district Wonosari.